Empowering the Bayu Segara Fishermen's Group through Digital Marketing: Enhancing Product Visibility and Sales in a Competitive Marketplace - Rahmansyah, Ahmad Iskandar; Hendra, Joni; Handayani, Dwi Iryaning; Masluha, Siti; Widianita, Nadia Putri; Hadiyanto, Mohammad; Fauzi, Rohmad (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
With a premium, halal-certified quick Ginger-Turmeric-Temulawak product, the Bayu Segara fishermen's organization has great difficulty growing their company. Important problems include underutilization of the potential of the product, poor digital expertise, limited manual marketing efforts, and limited promotional reach via WhatsApp. A thorough session covering digital marketing strategies—including social media management, online marketplace optimization, and content creation—was held on July 28 to help to solve these problems. Product photos done to improve e-commerce display before the training. The session gave attendees useful knowledge in social media account management, online store setup, and content creation. Practical experience helped them to use these abilities straight-forwardly, thereby enhancing their efforts at digital marketing. The findings show that product exposure, market reach, and sales should be much improved by the increased digital presence and marketing competencies. In a cutthroat digital market, this strategy offers the firm a viable road for corporate expansion.